Hydrogen uranyl arsenate hydrate single crystals: H2(UO2) 2(AsO4) +8 H2o. gel growth and characterization. - Manghi, E.; Polla, G. (North Holland Publishing Co., 1983)
Fil: Manghi, E. Comisión Nacional de Energía Atómica; Argentina